Adolescent Compulsive Sexual Behavior: Is It a Unique Psychological Phenomenon?. Issue 7 (3rd October 2018) - Efrati, Yaniv
ABSTRACT: Adolescent compulsive sexual behavior (CSB), and its associations with other personality predispositions (attachment orientations, temperament), gender, religiosity, and psychopathological tendencies, is the subject of this study. Five alternative empirical models were examined, all based on current theory and research on CSB. The sample included 310 high-school adolescents (183 boys, 127 girls), ranging in age from 16 to 18 years ( M = 16.94, SD = .65) and enrolled in the 11th (43.4%) and 12th (56.6%) grades, who completed self-report measures tapping CSB and the above mentioned variables. One model was found to be compatible with the data, indicating that CSB is an independent disorder from other psychopathological tendencies and is associated with religiosity, gender, temperament, and attachment orientations. Findings have implications for understanding the meaning of adolescent CSB as a psychological disorder and treating it differently from other disorders.